The Treatment of Cleidocranial Dysostosis (Scheuthauer-Marie-Sainton Syndrome), a Rare Form of Skeletal Dysplasia, Accompanied by Spinal Deformities: A Review of the Literature and Two Case Reports - Mehmet Bülent Balioğlu; Deniz Kargın; Akif Albayrak; Yunus Atıcı (Case Reports in Orthopedics)
Cleidocranial dysostosis is a skeletal dysplasia inherited in an autosomal dominant manner and may lead to complications such as scoliosis and kyphosis, concurrent with various orthopedic involvements. Since concurrent spinal deformities are of progressive nature, surgical treatment may be necessary. In addition to other orthopedic problems, possible accompanying complications such as atlanto-axial subluxation, myelopathy, syringomyelia, congenital spine deformities, spondylosis, and spondylolisthesis should be kept in mind while planning for the treatment of scoliosis and kyphosis. Lengthening the use of growth-friendly systems (growing rod) in patients, like ours, with an early onset of symptoms, and performing posterior instrumentation and fusion once the spinal growth is complete will yield successful results with no complications in the middle and the long term. Further multicenter studies with more comprehensive assessments are required to find solutions to spinal problems related to this rare skeletal dysplasia.